Investigating the PS seismic imaging of faults using seismic modelling and data from the Snøhvit field, Barents Sea - Jennifer Cunningham (11766300); Wiktor W. Weiball (11766303); Nestor Cardozo (11469946); David Iacopini (11766306) (2021)
Supplementary Material 1. Technical explanation of the forward seismic models.